From Text to Theatre: Reimagining Munakahat Education through Imersive Role-playing - Pramitha, Devi; Nikmah, Faridatun; Kamal, Abdullah; Anggarini, Ida Fitri; Noviyanti, Shobihatul Fitroh (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3116, 2024)
Munakahat education specifically for Madrasah student, the art of persuasive discourse practiced in South Asian and Middle Eastern traditions, has long captivated listeners with its intricate arguments and passionate delivery. However, traditional pedagogy often relies on static texts and rote memorization, failing to capture the dynamism and persuasiveness inherent in live debate fully. This research proposes a transformative approach: reimagining Munakhat education through immersive role-playing in one Madrasah in Indonesia. By merging text-based learning with interactive digital environments, this study explores the potential of virtual reality (VR) technology to foster deeper engagement and mastery of Munakhat skills. Participants practice Munakahat to enter captivating historical scenarios, embodying renowned Munakhat debaters of the past. Within these qualitative immersive settings, they will engage in real-time debates, formulate persuasive arguments, and hone their rhetorical skills in a context miming the charged atmosphere of actual Munakhat competitions. Through this innovative approach, Munakhat education transcends the confines of static texts and enters the vibrant realm of virtual theater. By empowering learners to step into the shoes of historical masters, this research reimagines Munakhat education as a dynamic and immersive journey, igniting a passion for persuasive discourse and cultural understanding.